CHARACTERISTICS OF JOSHUA AS A LEADER - Reymand M. Hutabarat (Fakultas Filsafat Universitas Advent Indonesia, 2016)
Leadership is one aspect that the world needed right now. As a Christian, biblicalleadership can be found in the bible in numerous characters. Christian leadership isan aspect that is rare and profound in this day and age. Mrs. White even stated aboutcharacteristics of the people who can stand for the right in the midst of a messyworld. Mrs. White said, “the greatest want of the world is the want of men—menwho will not be bought or sold, men who in their inmost souls are true and honest,men who do not fear to call sin by its right name, men whose conscience is as true toduty as the needle to the pole, men who will stand for the right though the heavensfall.”1The Bible mentions many people who possessed this trait of leadership, such asJoseph, Daniel, Paul, even Jesus Christ our Lord and Savior, but the concentration ofthis article is the man who succeeded Moses, which was Joshua.